Prevalence of over-the-counter medication use in pregnancy: a systematic review and meta-analysis - Kaeshaelya Thiruchelvam; Elly Uwajima; Sarinaa Marian Guna Selan; Shane Emmanuel James; Yu Xin Lai; E Lyn Lee; Chia Siang Kow (Discover Public Health)
Abstract Introduction Over-the-counter (OTC) medications are a popular choice for alleviating minor ailments during pregnancy. However, there are many risks associated with frequent and high use of OTC medications to the mother and foetus. Aims We performed a systematic review and meta-analysis to determine the prevalence of OTC medication use in pregnancy. Methods Electronic databases (Medline, Embase and Scopus) were systematically searched up to November 2023 to identify English-language articles with data on OTC medication use prevalence. Pooled prevalence (%) of OTC medication use with 95% confidence intervals (CI) were generated using a random-effects model. The quality of the studies was critically appraised using the Joanna Briggs Institute Critical Appraisal tool for use in systematic reviews for observational studies. Results Of the 20 studies included in the analyses, the majority (n = 13) were cross-sectional studies. The pooled prevalence of overall OTC medication use among pregnant women was 36% (95% CI 21%, 53%; n = 77,219). Pooled prevalence of overall analgesic use was 25% (95% CI 7%, 49%; n = 257,770). Highest individual OTC medications/medication classes were paracetamol use (32%; 95% CI 18%, 47%; n = 163,799) and antacid use (19%; 95% CI 8%, 32%; n = 1039). By trimesters, the pooled prevalence of OTC medication use was highest in the second trimester (30%; 95% CI 9%, 55%; n = 152,055), followed by the third trimester (25%; 95% CI 6%, 49%; n = 152,055), and the first trimester (19%; 95% CI 4%, 41%; n = 152,055). Conclusions The relatively high prevalence of OTC medication use among pregnant women is a cause for concern, but may be unavoidable. When known to healthcare providers, it is crucial to provide current, complete and accurate information about OTC medications to pregnant women. They should also be warned of the risks associated with OTC medications, and that if unsure, advice should be sought prior to use.